PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. USAHA KITA MAKMUR (UKM) KABUPATEN KUANTAN SINGINGI - Fitri, Elsa; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine how much influence of work motivation and work environment on employee performance at PT. Usaha Kita Makmur (UKM) Kuantan Singingi Regency. Samples in this study were taken as many as 56 respondents and techniques used Stratifield Random Sampling. The data used in this study using survey method through questionnaires and then processed to then processed with statistics through the program SPSS. The result of analysis using simple linear regression analysis (t test), and simultant significance test (test F) so that it can be seen that the variable of work motivation influence to employeeperformance variable, work enviroment variable affect to employee performance variable, and work motivation variable and the work environment affects simultaneuosly on employee performance. The calculation result known R Squre is the coefficient of determination and obtained the value of R squre of 0,724. That is, work motivation and work environment affect employee performance of 72,4%.Keyword : Work Motivation, Work environment, and Employee Performance